2017
DOI: 10.18632/oncotarget.20077
|View full text |Cite
|
Sign up to set email alerts
|

Jolkinolide B induces apoptosis of colorectal carcinoma through ROS-ER stress-Ca2+-mitochondria dependent pathway

Abstract: Colorectal carcinoma (CRC) remains one of the leading causes of death in cancer-related diseases. In this study, we aimed to investigate the anticancer effect of Jolkinolide B (JB), a bioactive diterpenoid component isolated from the dried roots of Euphorbia fischeriana Steud, on CRC cells and its underlying mechanisms. We found that JB suppressed the cell viability and colony formation of CRC cells, HT29 and SW620. Annexin V/PI assay revealed that JB induced apoptosis in CRC cells, which was further confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 43 publications
(52 reference statements)
0
22
0
Order By: Relevance
“…The intracellular alterations when cells suffer ischaemia, including H + and Ca 2+ accumulation and the corresponding dysfunctions, affect the mitochondrial membrane potential, leading to ROS formation [30,31]. In addition to these points, stress-response pathway activation would be induced by ROS accumulation immediately, and apoptosis would be subsequently increased [32]. Simultaneously, many apoptosis stimuli, including treatment with tumour necrosis factor (TNF)-α [33] and lipopolysaccharide (LPS) [34] and growth factor withdrawal, can induce ROS generation through mitochondria [35].…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular alterations when cells suffer ischaemia, including H + and Ca 2+ accumulation and the corresponding dysfunctions, affect the mitochondrial membrane potential, leading to ROS formation [30,31]. In addition to these points, stress-response pathway activation would be induced by ROS accumulation immediately, and apoptosis would be subsequently increased [32]. Simultaneously, many apoptosis stimuli, including treatment with tumour necrosis factor (TNF)-α [33] and lipopolysaccharide (LPS) [34] and growth factor withdrawal, can induce ROS generation through mitochondria [35].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the mitochondria-dependent apoptotic pathway can be activated by ER stress 20 22 . We explored whether the mitochondria-dependent apoptosis of H22 cells induced by PFEE-C and PFEE-W was mediated by ER stress.…”
Section: Resultsmentioning
confidence: 99%
“…However, cells will activate death programs when UPR fails. Recently, a large body of evidence has been shown that ER stress plays important roles in the induction of apoptosis 20 , 22 , 30 , 31 , which can activate JNK, promote caspase-12 cleavage and increase HSP70 level 32 34 . JNK can regulate some BCL-2 family proteins such as phosphorylation of Bcl-2 and Bim to cause Δψ m reduction, promote cytochrome c release and induce apoptosis 35 , 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Then the mixed protein samples were subjected to the in-solution digestion as previously described. [15,41] The digested peptides were desalinated using a MonoTIPTM C18 Pipette Tip (GL Sciences, Tokyo, Japan) and then analyzed with an Orbitrap Fusion Lumos mass spectrometer (Thermo Fisher Scientific) as previously described. [42] The raw MS data files were searched against UniProt-Swiss Human database (2017_03 Release) using Proteome Discoverer v2.1 (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%